Recent progress in high linearly fused polycyclic conjugated hydrocarbons (PCHs, n > 6) with well‐defined structures - Chen, Wangqiao (2020)
Although polycyclic conjugated hydrocarbons (PCHs) and their analogues have gained great progress in the fields of organic photoelectronic materials, the in‐depth study on present PCHs is still limited to hexacene or below because longer PCHs are insoluble, unstable, and tediously synthesized. Very recently, various strategies including on‐surface synthesis are developed to address these issues and many higher novel PCHs are constructed. Therefore, it is necessary to review these advances. Here, the recent synthetic approach, basic physicochemical properties, single‐crystal packing behaviors, and potential applications of the linearly fused PCHs (higher than hexacene), including acenes or π‐extended acenes with fused six‐membered benzenoid rings and other four‐membered, five‐membered or even seven‐membered and eight‐membered fused compounds, are summarized.